Juegos tradicionales en el desarrollo psicomotor de los niños de 4 años de la Unidad Educativa Darío C. Guevara - Guillin Parraga, Marife Jamilet (2023)
Traditional games, in addition to being a contribution to the culture of the people, are a recreational activity incident to the acquisition of motor skills in children from an early age, therefore an infant at 4 years old has the possibility of improving or acquiring new ones. skills while having fun with traditional games. In the present case study, the objective is to determine the influence of traditional games on the psychomotor development of 4-year-old children of the “Darío C. Guevara” Educational Unit, this having as a problem that currently many children prefer to spend their time with some technological device, and not entertain themselves with activities that contribute to their development, which is why it is essential that in educational centers, teachers propose activities that promote psychomotor skills at 4 years of age. As a methodology, it can be indicated that the type of descriptive research was applied, through which information was collected considering survey and interview techniques, for parents and the initial education teacher at the Darío C. Guevara Educational Unit, respectively. The results of the study reflected that at home the child is not encouraged to have fun with traditional games, while at school, the teacher believes it is feasible to apply traditional games to enhance psychomotor skills. In this way, it is concluded by indicating that traditional games are positive for a 4-year-old child, influencing their development in good shape, acquiring skills and gaining autonomy in their daily lives.